Application of the pulsating and continous water jet for granite erosion. (February 2020) - Tripathi, Rupam; Hloch, Sergej; Chattopadhyaya, Somnath; Klichová, Dagmar; Ščučka, Jiří; Das, Alok Kumar
Abstract: This research article aims at comparing the erosion performance of continuous and ultrasonically generated pulsating water jet technologies on granite samples at three pressure levels of 20 MPa, 40 MPa and 60 MPa. The granite surface was eroded using the circular nozzle of diameter d  = 1.9 mm with the variation of traverse speed at each pressure levels. The depth, width and volume erosion of the grooves generated by both the technologies were evaluated using surface profilometer. It was evident from the results, that the variations in the process parameters show the influential behaviour on the erosion performance of granite by pulsating water jet in comparison to the continuous water jet. The optical microscopy and scanning electron microscopy (SEM) of the generated grooves were analysed to observe the surface morphology and plastic deformation phenomenon during the erosion of the granite samples. The above study shows that the pulsating water jet technology is the preferable approach over continuous water jet that can be utilised for different manufacturing applications. Also, the technology is economically more beneficial than the presently used cleaner technologies (non-abrasive and abrasive) as it reduces the extra cost invested in high-pressure pumps.